성인여성의 주관적 체형인식이 삶의 질에 미치는 영향 - 김다현; Kim Da-hyun; 김계수; Kim Gye-soo; 김은희; Kim Eun-hee; 유은희; Yoo Eun-hee; 전다솜; Jeon Da-som; 한채정; Han Chae-jeong (국제문화예술, 2023)
연구목적: 본 연구의 목적은 20세∼64세 성인여성의 주관적 체형 인식이 삶의 질에 미치는 영향을 파악하고 이들의 상관관계를 분석하고 주관적 체형 인식에 미치는 영향요인을 알아보고자 한 조사 연구다. 연구방법: 연구 대상자는 국내에 거주중인 20세 부터 64세 대상으로 하였다. 자료수집 기간은 2022년 5월 26일부터 6월 22일까지 조사하였으며, 총 410명에게 설문지를 배부하여, 이들 응답자 중 불성실한 응답자 17명을 제외한 393명을 대상으로 하였다. 모든 자료는 SPSS WIN 21.0 프로그램을 이용하여 빈도 분석을 하였다. 연구결과: 연구결과는 첫째, 연구대상자의 연령과 결혼상태, 최종학력, 직업, 월 소득에 따른 주관적 체중 인식의 차이는 모두 유의수준 5%에서 유의미하지 않았다. 둘째, 주관적 체중 인식을 살펴본 결과는 주관적 체중 인식 전체의 평균은 3.73으로 체중조절이 필요(M=3.87)하다, 환경에 체중 조절에 영향을 준다, 체중조절에 관심이 많다, 체중이 비만이다, 체중의 변화가 (M=3.62) 있다, 순으로 평균이 높았다. 연구대상자 특성에 따른 삶의 질의 차이를 살펴본 결과 연령은 40대(M=3.59), 50대, 20대, 30대, 60대(M=3.14) 순으로 40대의 삶의 질이 가장 높았고, 60대의 삶의 질이 가장 낮았다(F=3.259, p<.05). 셋째, 주관적 체중 인식과 삶의 질은 주관적 체중 인식(r=. 537, p<.001)과 매우 높은 수준의 상관이 있는 것으로 확인하였다. 넷째, 대상자의 주관적 체중 인식이 삶의 질에 미치는 영향을 알아보기 위하여 단순 회귀분석을 한 결과, =0.289로 전체 변동의 28.9%로 회귀모형을 설명하고 있음을 알 수 있었다. 결론: 본연구의 결론은 성인여성의 연령에 따라 다소 차이가 있지만, 체중조절을 더 시도하는 것은 자신의 실제 체형을 왜곡 인식하여 체형에 불만족에 따른 삶의 질 하락, 스트레스가 높음을 알 수 있었다. 이에 따라서 올바른 신체상을 확립하기 위해선 마른 몸매 선호에 대한 왜곡된 사회문화적 분위기를 개선하고 자신의 체형에 대한 올바른 인식이 필요함을 확인하였다. Purpose: The purpose of this study is to identify the effect of subjective body type perception on the quality of life of adult women aged 20 to 64, analyze their correlations, and find out the factors affecting subjective body type perception. Methods: The subjects of the study were those aged 20 to 65 living in Korea. The data collection period was surveyed from May 26 to June 22, 2022, and questionnaires were distributed to a total of 410 people, targeting 393 of these respondents, excluding 17 who did not respond faithfully. All data were analyzed using the SPSS WIN 21.0 program. Result: First, the study's findings showed that the difference in subjective weight perception according to the study's age, marital status, final education, occupation, and monthly income was not significant at the significance level of 5%. Second, as a result of examining subjective weight recognition, the average of the entire subjective weight recognition is 3.73, which requires weight control (M=3.87), affects weight control in the environment, and is interested in weight control. be overweight. There is a change in weight M=3.62. The average was high in order. In addition, as a result of examining the differences in quality of life according to the characteristics of the study subjects, the age was the highest in their 40s (M=3.59), 50s, 20s, 30s, and 60s (M=3.14), and the quality of life in their 60s was the lowest (F=3.259, p<.05). Third, subjective weight recognition and quality of life are subjective weight recognition (r=. 537, p<.It was confirmed that there was a very high positive correlation with 001). Fourth, as a result of a simple regression analysis to find out the effect of subjective weight recognition on the quality of life, it can be seen that R = 0.289 explains the regression model at 28.9% of the total variation. Conclusion: Although the conclusion of this study varies somewhat depending on the age of adult women. Trying to control weight more distortedly recognizes one's actual execution, and it can be seen that the quality of life decreases and the stress experience rate is high due to dissatisfaction with the body type. Accordingly, in order to confirm the right body image, it was confirmed that the distorted socio-cultural atmosphere for skinny body preferences was improved and the right perception of one's body type was needed.